Maintenance of genetic variation and panmixia in the commercially exploited western rock lobster (Panulirus cygnus) - Kennington, W.; Cadee, S.; Berry, O.; Groth, David; Johnson, M.; Melville-Smith, Roy (Springer, 2013)
Marine species with high fecundities and mortalities in the early life stages can have low effective population sizes, making them vulnerable to declines in genetic diversity when they are commercially harvested. Here, we compare levels of microsatellite and mitochondrial sequence variation in the western rock lobster (Panulirus cygnus) over a 14-year period to test whether genetic variation is being maintained. Panulirus cygnus is a strong candidate for loss of genetic variation because it is a highly fecund species that is likely to experience high variance in reproductive success due to an extended larval planktonic stage. It also supports one of the largest and most economically important fisheries in Australia, with landings of between 8,000 and 14,500 tons (~70 % of the total legal-sized biomass) being harvested in some years. We found remarkably high levels of genetic variation in all samples and no evidence of a decline in genetic diversity over the time interval we studied. Furthermore, there was no evidence of a recent genetic bottleneck, and effective population size estimates based on single sample and temporal methods were infinitely large. Analysis of molecular variance indicated no significant population structure along 960 km of coastline or genetic differentiation among temporal samples. Our results support the view that P. cygnus is a single, panmictic population, and suggest genetic drift is not strong enough to reduce neutral genetic diversity in this species if current management practices and breeding stock sizes are maintained.